(untitled) (Pedagogy of Higher and Secondary Education, 2007)
In the article an author examines the problem of polyart education of future music, perfection of process of integral awareness of artistic features of synthetic genre - ballet masters. Methodical recommendations to realization ofpolyart approach in the process of consideration of ballet «Forest song» of M. Skorulskyj are offered.